IMPLEMENTATION OF COMPREHENSIVE REHABILITATION MEASURES FOR MILITARY SERVICEMEN IN THE HOTEL ENTERPRISE - Панова, А.В.; Пушка, О.С.; Шаран, Л.О. (SWorldJournal, 2024)
The article examines the importance of implementing a comprehensive program of rehabilitation of military personnel in hotel enterprises of the health sector. The complex of services focused on the physical recovery and psychological support of military p